Computer-Aided Document Indexing Accessing Legislation: A Joint Venture of Flanders and Croatia - Tadić, Marko (Array, 2009)
This book presents a collection of selected relevant papers that were published during the CADIAL (Computer-Aided Document Indexing for Accessing Legislation) project. Taken as a whole, this collection represents a thorough description of the motivations, methods, procedures, and results of the project within the covers of a single book. The chapters of this book are composed of these papers, and while some were simply corrected, others were rewritten to a certain degree, and some are being published here for the first time. We believe that this book presents the overall goal of the project – the construction of a durable infrastructure for a publicly accessible service for automatic indexing and retrieval from a database of 20, 000 official documents of the Republic of Croatia – along with the way this goal was achieved.